Autonomous magnetic labelling of functional mesenchymal stem cells for improved traceability and spatial control in cell therapy applications. (6th May 2016) - Harrison, Richard; Markides, Hareklea; Morris, Robert H.; Richards, Paula; El Haj, Alicia J.; Sottile, Virginie
Abstract: Mesenchymal stem cells (MSCs) represent a valuable resource for regenerative medicine treatments for orthopaedic repair and beyond. Following developments in isolation, expansion and differentiation protocols, efforts to promote clinical translation of emerging cellular strategies now seek to improve cell delivery and targeting. This study shows efficient live MSC labelling using silica‐coated magnetic particles (MPs), which enables 3D tracking and guidance of stem cells. A procedure developed for the efficient and unassisted particle uptake was shown to support MSC viability and integrity, while surface marker expression and MSC differentiation capability were also maintained. In vitro, MSCs showed a progressive decrease in labelling over increasing culture time, which appeared to be linked to the dilution effect of cell division, rather than to particle release, and did not lead to detectable secondary particle uptake. Labelled MSC populations demonstrated magnetic responsiveness in vitro through directed migration in culture and, when seeded onto a scaffold, supporting MP‐based approaches to cell targeting. The potential of these silica‐coated MPs for MRI cell tracking of MSC populations was validated in 2D and in a cartilage repair model following cell delivery. These results highlight silica‐coated magnetic particles as a simple, safe and effective resource to enhance MSC targeting for therapeutic applications and improve patient outcomes. © 2016 The Authors Journal of Tissue Engineering and Regenerative Medicine Published by John Wiley & Sons Ltd.